19. PGT-A: WHEN IT IS BETTER NOT TO KNOW. (August 2019) - Maximilian, S.; Barbara, W.; Astrid, S.; Jasmin, O.; Delf, S.; Martin, Z.; Maximilian, M.
Abstract : Introduction: PGT-A was implemented to select euploid embryos and thus, to improve IVF-outcome in terms of higher live birth rate (LBR), lower miscarriage rate or shorter time-to-pregnancy. With the implementation of refined techniques such as Next Generation Sequencing (NGS) the resolution to detect (small) chromosomal aberrations in embryos increased. This holds true for as chromosomal mosaicism as well as for segmental aberrations, and consequently the amount of embryos tested as euploid decreases. This observation highlights the complex nature of genetic (in)stability during early embryogenesis and reveals the substantial shortcomings of PGT-A. The early genetic plasticity counteracts with the primary goal to improve LBR. The aim of the study was to determine when PGT-A can be recommended considering the drop-out rate starting from non-biopsable embryos, amplification failure and drop-out due to testing as non-euploid. Patients, material & methods: This retrospective single-center study (2016-2018) includes 173 hormonal stimulation cycles (71 patients). PGT-A was performed either due to three unsuccessful embryo transfers or due to three miscarriages in the patient's history. Patients with tested structural chromosomal aberrations as well as donor cycles were excluded. Blastocyst culture was performed in single step culture medium in the Embryoscope. TE-biopsy was performed on day 5-7. WGA was performed either by PicoPlex (Rubicon Genomics) or by SurPlex (BlueGenome/ Illumina). NGS was processed using VeriSeq platform with data analysis by BlueFuse Multi (Illumina). Results: A total of 1, 751 MII oocytes resulted in 752 blastocysts. TE-biopsy of at least one blastocyst was performed in 157 cycles (68 patients). This resulted in 609 biopsied blastocysts of which 57 showed either failure of amplification or defective sequencing. 156 (25.6%) samples showed either whole chromosome aneuploidies or uniform segmental chromosomal aberrations. Further, 117 (19.2%) biopsies revealed either chromosomal or segmental mosaicism and, 140 (23.0%) were tested with a combination of uniform and mosaic aberrations. Finally, 139 (22.8%) samples were tested as chormosomally normal. This results in mean 0.8 blastocysts/cycle tested as known euploid compared to originally 4.5 blastocysts/cycle. Conclusions: High embryo losses due to non-biopsable blastocysts, amplification failure and non-interpretable results are well known but often neglected. Additionally, while NGS allows high resolution for small structural or numerical chromosomal aberrations as mosaic, the number of transferable blastocysts decreases enormous too. Chromosomal mosaicism (euploid/aneuploid) is a major problem of PGT-A, additional problems arises from segmental chromosomal aberrations that can be present as mosaic as well. When PGT-A is recommended IVF-patients, physicians have to inform about high costs for patients, the increased number of IVF-cycles needed and the high cancellation rates. When estimating a 60% baby-take home rate after PGT-A the same number of babies would be born starting with 752 untested blastocysts considering an only 11% baby-take home rate (83.4 vs. 82.7 babies). This comparison shows that counselling for PGT-A due to RIF or RM has to be well prepared.